The Pearl - Dimmock, Jessica; LaMarca, Christopher (USA, 2016)
The film explores the emotional and physical experience of being a middle-aged to senior transgender woman against the backdrop of post-industrial logging towns in the Pacific Northwest.
Verzio Film Festival Submission
Keywords: Documentary films